2002
DOI: 10.1159/000063083
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Iodine Supply: Representative Data on Intake and Urinary Excretion of Iodine from the German Population in 1996

Abstract: Background/Methods: In Germany, iodine deficiency is common. In a representative group of 2,500 Germans (age 1 13 years), using a specially designed food questionnaire, the iodine intake was calculated. In addition, iodine and creatinine concentrations in spot urine samples were determined in three groups with a possibly increased risk of iodine deficiency (769 conscripts, 886 pairs of mothers and newborns) or future hyperthyroidism (574 adults, age range 50-70 years) from 26 representative regions. In four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 16 publications
3
26
0
6
Order By: Relevance
“…Moreover, the statistical bias in large cohorts (. 500 probands) is lower when using mean values than median values as mean values better describe metric variables than the median values (25,26). Multivariable comparisons between the groups were performed with ANOVA (endpoints thyroid volume and urinary I 2 excretion).…”
Section: Methodsmentioning
confidence: 98%
“…Moreover, the statistical bias in large cohorts (. 500 probands) is lower when using mean values than median values as mean values better describe metric variables than the median values (25,26). Multivariable comparisons between the groups were performed with ANOVA (endpoints thyroid volume and urinary I 2 excretion).…”
Section: Methodsmentioning
confidence: 98%
“…The daily intake of iodine has been calculated in several studies in The Netherlands and found to be in the range of 85 -293 mg 34 . The mean intake of iodine is calculated to be approximately 340 mg day 21 in Finland 31 and 119 mg day 21 in Germany 35 . In the UK the daily iodine intake was found to be in the range of 166-277 mg in studies carried out from 1985 to 1997 36 -38 .…”
mentioning
confidence: 99%
“…Two studies detected a circadian rhythm in UI concentrations [2,29], whereas two others did not [1,28]. In one study [30], a significant circadian rhythm of ICR was found, with the highest excretion in the late afternoon – 25.8% more than between 7 and 10 a.m. – indicating a dependence of ICR on lunch. Rasmussen et al [1] suggested avoiding non-fasting samples in the morning since UI excretion concentrations seemed to be lowest then.…”
Section: Discussionmentioning
confidence: 99%